Active sites of copper-complex catalytic materials for electrochemical carbon dioxide reduction - Weng, Zhe; Wu, Yueshen; Wang, Maoyu; Jiang, Jianbing; Yang, Ke; Huo, Shengjuan; Wang, Xiao-Feng; Ma, Qing; Brudvig, Gary W.; Batista, Victor S.; Liang, Yongye; Feng, Zhenxing; et al. (Nature communications, 2018)
Restructuring-induced catalytic activity is an intriguing phenomenon of fundamental importance to rational design of high-performance catalyst materials. We study three copper-complex materials for electrocatalytic carbon dioxide reduction. Among them, the copper(II) phthalocyanine exhibits by far the highest activity for yielding methane with a Faradaic efficiency of 66% and a partial current density of 13 mA cm −2 at the potential of – 1.06 V versus the reversible hydrogen electrode. Utilizing in-situ and operando X-ray absorption spectroscopy, we find that under the working conditions copper(II) phthalocyanine undergoes reversible structural and oxidation state changes to form ~ 2 nm metallic copper clusters, which catalyzes the carbon dioxide-to-methane conversion. Density functional calculations rationalize the restructuring behavior and attribute the reversibility to the strong divalent metal ion–ligand coordination in the copper(II) phthalocyanine molecular structure and the small size of the generated copper clusters under the reaction conditions. The catalytic conversion of carbon dioxide into value-added products requires an understanding of the active species present under working conditions. Here, the authors discover copper-containing complexes to reversibly transform during electrocatalysis into methane-producing copper nanoclusters.